2017
DOI: 10.12791/ksbec.2017.26.4.235
|View full text |Cite
|
Sign up to set email alerts
|

Development of Growth Models as Affected by Cultivation Season and Transplanting Date and Estimation of Prediction Yield in Kimchi Cabbage

Abstract: This study was carried out to estimate growth characteristics of Kimchi cabbage cultivated in two different growing seasons and three transplanting dates in the greenhouses, and to create a predicting model for the production of Kimchi cabbage based on the growth parameters and climatic elements. Kimchi cabbages were transplanted three times at intervals of two weeks in spring and autumn growing seasons. Sigmoidal models for the estimation of fresh weight (Fw) was designed with days after transplanting, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…In the Republic of Korea, kimchi cabbage is typically transplanted for the autumn season in late August to early September and harvested between late November and early December. A study on kimchi cabbage weight prediction models based on transplanting dates indicated that kimchi cabbages transplanted in early September had lower weights compared to cabbages transplanted two weeks earlier [60]. When applying the growth model for each transplanting date with a two-year average cultivation duration.…”
Section: Suggestion 1: Early Transplanting Strategymentioning
confidence: 99%
“…In the Republic of Korea, kimchi cabbage is typically transplanted for the autumn season in late August to early September and harvested between late November and early December. A study on kimchi cabbage weight prediction models based on transplanting dates indicated that kimchi cabbages transplanted in early September had lower weights compared to cabbages transplanted two weeks earlier [60]. When applying the growth model for each transplanting date with a two-year average cultivation duration.…”
Section: Suggestion 1: Early Transplanting Strategymentioning
confidence: 99%